The great math mystery [videorecording (DVD)] - McCabe, Daniel; Livio, Mario, 1945-; Sanders, Jay O., 1953- (PBS Distribution, 2015)
Astrophysicist Mario Livio, along with a colorful cast of mathematicians, physicists, and engineers, follow math from Pythagoras to Einstein and beyond, all leading to the ultimate riddle: Is math an invention or a discovery? Humankind's clever trick, or the language of the universe? Join Nova for a mathematical mystery tour, a provocative exploration of math's astonishing power across the centuries.